Mothers, Monsters, Heroes and Whores: Reinscribing Patriarchy in European Holocaust Films. Issue 2 (3rd May 2016) - Waterhouse-Watson, Deb; Brown, Adam
Abstract : This article examines the portrayal of female Gentile rescuers in Holocaust films. We analyze two recent and somewhat unconventional Eastern European films, Agnieszka Holland's In Darkness (Poland, 2011) and Jan Hrebejk's Divided We Fall (Czech Republic, 2000), which, to varying degrees, disrupt conventional narratives of selfless heroism and avoid the eroticized objectification of women common in many (particularly American) Holocaust films. Nevertheless, a detailed analysis reveals how these films also marginalize or erase women's roles as rescuers, either in preference to narratives of dominative masculine heroism or in order to undertake a politico-religious appropriation of the Holocaust, each of which implicitly excludes and exploits the feminine. In both cases, the films trivialize women's particular and complex historical experiences, including sexual violence, and subordinate them to masculine interests.